Repair of Congenital Heart Disease with Associated Pulmonary Hypertension in Children: What are the Minimal Investigative Procedures? Consensus Statement from the Congenital Heart Disease and Pediatric Task Forces, Pulmonary Vascular Research Institute (PVRI). (1st June 2014) - Lopes, Antonio Augusto; Barst, Robyn J.; Haworth, Sheila Glennis; Rabinovitch, Marlene; Dabbagh, Maha Al; del Cerro, Maria Jesus; Ivy, Dunbar; Kashour, Tarek; Kumar, Krishna; Harikrishnan, S.; D'Alto, Michele; Thomaz, Ana Maria; et al.
Abstract : Standardization of the diagnostic routine for children with congenital heart disease associated with pulmonary arterial hypertension (PAH‐CHD) is crucial, in particular since inappropriate assignment to repair of the cardiac lesions (e.g., surgical repair in patients with elevated pulmonary vascular resistance) may be detrimental and associated with poor outcomes. Thus, members of the Congenital Heart Disease and Pediatric Task Forces of the Pulmonary Vascular Research Institute decided to conduct a survey aimed at collecting expert opinion from different institutions in several countries, covering many aspects of the management of PAH‐CHD, from clinical recognition to noninvasive and invasive diagnostic procedures and immediate postoperative support. In privileged communities, the vast majority of children with congenital cardiac shunts are now treated early in life, on the basis of noninvasive diagnostic evaluation, and have an uneventful postoperative course, with no residual PAH. However, a small percentage of patients (older at presentation, with extracardiac syndromes or absence of clinical features of increased pulmonary blood flow, thus suggesting elevated pulmonary vascular resistance) remain at a higher risk of complications and unfavorable outcomes. These patients need a more sophisticated diagnostic approach, including invasive procedures. The authors emphasize that decision making regarding operability is based not only on cardiac catheterization data but also on the complete diagnostic picture, which includes the clinical history, physical examination, and all aspects of noninvasive evaluation.